2023
DOI: 10.3390/biomedicines11020334
|View full text |Cite
|
Sign up to set email alerts
|

iPSC-Derived Cardiomyocytes in Inherited Cardiac Arrhythmias: Pathomechanistic Discovery and Drug Development

Abstract: With the discovery of induced pluripotent stem cell (iPSCs) a wide range of cell types, including iPSC-derived cardiomyocytes (iPSC-CM), can now be generated from an unlimited source of somatic cells. These iPSC-CM are used for different purposes such as disease modelling, drug discovery, cardiotoxicity testing and personalised medicine. The 2D iPSC-CM models have shown promising results, but they are known to be more immature compared to in vivo adult cardiomyocytes. Novel approaches to create 3D models with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 129 publications
0
2
0
Order By: Relevance
“…These hiPSCs can be differentiated into cardiomyocytes (hiPSC-CMs), which can be examined within microphysiological systems, often referred to as organs on a chips 52 , 53 . Specifically, these systems hold considerable potential for detecting undesirable side effects of emerging drug compounds 54 56 .…”
Section: Discussionmentioning
confidence: 99%
“…These hiPSCs can be differentiated into cardiomyocytes (hiPSC-CMs), which can be examined within microphysiological systems, often referred to as organs on a chips 52 , 53 . Specifically, these systems hold considerable potential for detecting undesirable side effects of emerging drug compounds 54 56 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, electrophysiological and transcriptomic studies have demonstrated that hiPSC-CMs express SK channels ( Zhao et al, 2018 ; Simons et al, 2023 ). However, the expression of SK channels in hiPSC-aCMs has not been studied.…”
Section: Hipsc-cms As a Model For The Study Of Sk Channel Risk Variantsmentioning
confidence: 99%